CONCEPTION OF THE AERO CLUB ESTABLISHMENT - І. М. Нєнно (Ринкова економіка: сучасна теорія і практика управління)
Practical recommendations for the establishment of Ukrainian aero club were presented. An approach to the organization and promotion of aero club services portfolio were developed. The possible sources of funding were considered, a competitive analysis and SWOT-analysis of the market of training, air taxi services market and entertainment with key participants was made.